ANALISIS LAPORAN KEUANGAN UNTUK MENGUKUR KINERJA KEUANGAN PERUSAHAHAN - Ahmad Nurdin Hasibuan; Muhammad Muhammad; Abdul Wahab Samad (Universitas Prof. Dr. Moestopo (Beragama), 2022)
The research method uses quantitative descriptive in assessing the financial performance of PT Karya Indo Selera for the 2016-2020 period. The results showed that the net profit margin at the company PT Karya Indo Selera can be seen that the company's financial performance is not in a good condition, because it is still below the average standard. Return on assets can be seen that the company's financial performance is in poor condition, because it is still below the average. Return on equity can be seen that the company's financial performance is not in good condition, because it is still below the average standard. The current ratio of the company can be seen that the company's financial performance is not in a good condition, because it is still below the average. Quick ratio can be seen that the company's financial performance is not in good condition. Debt to asset ratio can be seen that the company's financial performance is in good condition because the average value of this ratio is still above the industry standard. Debt to equity ratio can be seen that the company's financial performance is in good condition because the average value of this ratio is still above the industry standard. This means that half of the company's assets are financed by capital compared to debt. The total asset turnover can be seen that the company's financial performance is in good condition because the average value of the ratio reaches industry standards. Fixed asset turnover can be seen that the company's financial performance is in good condition because the average value of the ratio exceeds the average industry standard. With a good value it can be interpreted that the company has an increase that exceeds the industry average ratio.